The effect of using a feedback device in teaching a skill such as standing on the hands and switching a half turn outward on the parallel bar - boubakre nouiri; Nada Al-Saedeey; Ayad Salman; Jamal hamza (College of Physical Education and Sport Sciences, 2024)
Two general trainers in the sports field do not disagree about finding and using a special aid in teaching skills, as each sports skill has a specificity in learning it, and the game of artistic gymnastics for men is one of the individual games and has physical, movement and coordination requirements. The aim of the research is to know the effect of using The feedback device in teaching the skill of standing on the hands, alternating a half-turn outward on the parallel apparatus. The research hypothesis is that the use of an instantaneous feedback device has an effect in teaching the skill of standing on the hands, alternating a half-turn outward on the parallel apparatus. The researcher used the experimental method with a sample design. One because it suits the research problem, as the research population is limited to (7) emerging players who train in Baghdad, Al-Amana Sports Club for Gymnastics, and their ages range between (9-13) years. As for the research sample, they are (6) players, and the research sample constituted (90%). As for the most important conclusions, the assistive device added to the sample a second and enjoyable training method that had a clear impact on learning the skill of standing on the hands, switching half a turn to the outside. Through the educational units and repetitions for the players on the device, it becomes clear that it has a good design and can withstand their weights and repetitions. The researcher suggests that During the course of working on some skills similar to the skill under research, conducting studies on the use of an assistive device in learning them, in which the handstand skill enters the elementary part, such as the skill of hilly and switching half a turn inwards, which have greater difficulties in learning.